Expression of survivin does not appear to influence breast cancer recurrence risk. (1st February 2019) - Collin, Lindsay J.; Cronin-Fenton, Deirdre P.; Ahern, Thomas P.; Christensen, Kristina B.; Damkier, Per; Hamilton-Dutoit, Stephen; Kjaersgaard, Anders; Lauridsen, Kristina L.; Yacoub, Rami; Christiansen, Peer; Sørensen, Henrik Toft; Lash, Timothy L.
Abstract: Background: Survivin is an inhibitor of apoptosis, and its expression associates with poor outcomes in multiple cancers. It may be a therapeutic target due to its unique expression in cancer cells. Methods: We estimated the association between nuclear and cytoplasmic survivin expression in primary tumors and breast cancer recurrence. In this case-control study, we included women age 35–69, diagnosed with stage I–III breast cancer between 1985 and 2001, and registered with the Danish Breast Cancer Group. We identified 541 patients with breast cancer recurrence with estrogen receptor–positive disease who were treated with tamoxifen for at least 1 year (ER+/TAM+) and 300 with estrogen receptor–negative carcinomas, not treated with tamoxifen, and who survived at least 1 year (ER−/TAM−). Controls were matched to cases on ER/TAM status, date of surgery, menopausal status, stage and county. Survivin expression was estimated by immunohistochemistry on tissue microarrays. We fit logistic regression models to estimate odds ratios (ORs) and 95% confidence intervals (CIs) associating nuclear and cytoplasmic survivin expression with recurrence. Results: Associations between nuclear and cytoplasmic survivin expression and breast cancer recurrence were near-null in both ER+/TAM + and ER−/TAM − strata. For the cytoplasmic to nuclear ratio (CNR) of survivin expression, we found a null association in the ER+/TAM + group comparing CNR ≥5 with CNR <5, but an association (OR =2.48, 95% CI: 1.15, 5.31) in the ER−/TAM − group. Conclusions: Survivin expression was not associated with breast cancer recurrence in this study. The CNR ratio may warrant further investigation especially among ER − tumors.